Question
upstudy study bank question image url

\[ \begin{array}{l}\text { Find the real solutions, if any, using the quadratic formula. } \\ 3 x^{2}-13 x+14=0\end{array} \] Select the correct choice below and fill in any answer boxes in your choice. A. The solution set is \( \left\{\begin{array}{l}\text { B. The solution is not a real number. } \\ \text { (Simplify your answer. Use a comma to separate answers as needed.) }\end{array}\right. \)

Ask by Lawson Deleon. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 2 \) and \( x = \frac{7}{3} \).

Solution

To find the real solutions to the quadratic equation \( 3x^2 - 13x + 14 = 0 \) using the quadratic formula, follow these steps: **Quadratic Formula:** \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] **Given Equation:** \[ 3x^2 - 13x + 14 = 0 \] Here, \( a = 3 \), \( b = -13 \), and \( c = 14 \). **Step 1: Calculate the Discriminant (\( \Delta \)):** \[ \Delta = b^2 - 4ac \] \[ \Delta = (-13)^2 - 4(3)(14) \] \[ \Delta = 169 - 168 \] \[ \Delta = 1 \] Since the discriminant is positive (\( \Delta > 0 \)), there are two distinct real solutions. **Step 2: Apply the Quadratic Formula:** \[ x = \frac{-(-13) \pm \sqrt{1}}{2 \times 3} \] \[ x = \frac{13 \pm 1}{6} \] **Solution 1:** \[ x = \frac{13 + 1}{6} = \frac{14}{6} = \frac{7}{3} \] **Solution 2:** \[ x = \frac{13 - 1}{6} = \frac{12}{6} = 2 \] **Final Answer:** **A. The solution set is \( 2, \frac{7}{3} \).**

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the solutions to the quadratic equation \( 3x^2 - 13x + 14 = 0 \), we can use the quadratic formula, which is given by: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] In our case, \( a = 3 \), \( b = -13 \), and \( c = 14 \). First, we calculate the discriminant \( b^2 - 4ac \): \[ b^2 - 4ac = (-13)^2 - 4(3)(14) = 169 - 168 = 1 \] Since the discriminant is positive, we can find two real solutions. Now plugging the values into the quadratic formula: \[ x = \frac{-(-13) \pm \sqrt{1}}{2 \cdot 3} = \frac{13 \pm 1}{6} \] Calculating the two potential solutions: 1. \( x = \frac{13 + 1}{6} = \frac{14}{6} = \frac{7}{3} \) 2. \( x = \frac{13 - 1}{6} = \frac{12}{6} = 2 \) So, the solution set is \( \left\{ \frac{7}{3}, 2 \right\} \). A. The solution set is \( \left\{ \frac{7}{3}, 2 \right\} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy